Preclinical evaluation of nanoparticle albumin‐bound paclitaxel for treatment of pediatric bone sarcoma. Issue 11 (19th April 2014) - Wagner, Lars M.; Yin, Hong; Eaves, David; Currier, Mark; Cripe, Timothy P.
ABSTRACT The combination of docetaxel and gemcitabine is frequently used to treat recurrent bone sarcoma. Nanoparticle albumin‐bound paclitaxel (nab‐paclitaxel) is less toxic and more active than docetaxel or paclitaxel for breast cancer patients. The combination of nab‐paclitaxel and gemcitabine has preclinical synergy and is approved to treat pancreatic cancer. We observed growth inhibition and improved survival with nab‐paclitaxel in a Ewing sarcoma xenograft, and activity was additive with gemcitabine in an osteosarcoma model. Primary Ewing sarcoma tumors expressed the transport protein SPARC, previously associated with nab‐paclitaxel activity. These findings provide rationale for further evaluation of nab‐paclitaxel with gemcitabine for bone sarcoma. Pediatr Blood Cancer 2014;61:2096–2098. © 2014 Wiley Periodicals, Inc.